Curable polymer composition and laminate

A curable polymer composition with specific solubility parameter and molecular weight ratios forms a hard coat layer with enhanced anti-glare and stretchability, addressing the limitations of existing methods.

JP7601077B2Active Publication Date: 2024-12-17MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022176709
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-02
Publication Date
2024-12-17
Estimated Expiration
2038-01-31

AI Technical Summary

Technical Problem

Existing methods for imparting anti-glare properties to image display devices suffer from insufficient stretchability and surface scratch resistance.

Method used

A curable polymer composition comprising polymers with different solubility parameters and unsaturated double bonds, along with a polyfunctional (meth)acrylate, is used to form a hard coat layer with specific solubility and molecular weight ratios, ensuring phase separation and increased crosslinking for improved anti-glare and scratch resistance.

Benefits of technology

The composition achieves a hard coat layer with excellent anti-glare properties and stretchability, maintaining gloss consistency and scratch resistance during stretching.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601077000001
    Figure 0007601077000001
  • Figure 0007601077000002
    Figure 0007601077000002
Patent Text Reader

Abstract

The present invention addresses the problem of providing a curable polymer composition capable of forming a hard coat layer having excellent antiglare properties and stretchability, and a laminate having a cured coating film of the composition. [Solution] A curable polymer composition comprising a polymer A, a polymer B which has a solubility parameter (SP value) different from that of the polymer A and is incompatible with the polymer A, and a polyfunctional (meth)acrylate C, wherein the curable polymer composition satisfies the following (1) and (2): (1) SPA-SPB≧0.5 (2) Polymer A has an unsaturated double bond and the double bond equivalent is 0.1 mmol / g or more and 4 mmol / g or less. (SPA and SPB represent the solubility parameters of the polymer A and the polymer B, respectively.)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable polymer composition capable of forming a hard coat layer having excellent antiglare properties and stretchability, and to a laminate having a cured coating film thereof. [Background technology]

[0002] As a technique for imparting anti-glare properties to the surface of an image display device such as a touch panel display, a method is known in which a film having fine irregularities on its surface is insert-molded simultaneously with molding of a resin molded body such as a display. For example, Patent Document 1 describes an anti-glare film in which unevenness is expressed on the surface by using a composition containing two types of polymers with different SP values ​​(solubility parameters). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-49748 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the method described in Patent Document 1 has insufficient stretchability during molding and insufficient scratch resistance on the surface. The present invention aims to solve these problems. [Means for solving the problem]

[0005] That is, the present invention includes the following [1] to [9].

[0006] [1] A curable polymer composition comprising a polymer A, a polymer B having a solubility parameter (SP value) different from that of the polymer A and incompatible with the polymer A, and a polyfunctional (meth)acrylate C, the curable polymer composition satisfying the following (1) and (2): (1) SPA-SPB≧0.5 (2) Polymer A has an unsaturated double bond and a double bond equivalent of 0.1 mmol / g or more and 4 mmol / g or less. (SPA and SPB represent the solubility parameters of the polymer A and the polymer B, respectively.) [2] The curable polymer composition according to [1], which satisfies the following (3): (3) SPC-SPB≦(SPA-SPC)×2.5 (SPC indicates the solubility parameter of the polyfunctional (meth)acrylate C.) [3] The curable polymer composition according to [1] or [2], wherein the weight average molecular weight of the polymer A is more than 2,000 and not more than 200,000. [4] The curable polymer composition according to any one of [1] to [3], wherein the weight average molecular weight of the polymer B is more than 2,000 and not more than 200,000. [5] The curable polymer composition according to any one of [1] to [4], comprising an organic solvent (solvent X) which is a good solvent for both polymer A and polymer B, and an organic solvent (solvent Y) which is a good solvent for polymer A but a poor solvent for polymer B. [6] The curable polymer composition according to any one of [1] to [5], wherein the content of polymer A is 30 to 90 parts by mass, the content of polymer B is 5 to 40 parts by mass, and the content of polyfunctional (meth)acrylate C is 1 to 49 parts by mass, per 100 parts by mass of the curable polymer composition. [7] The curable polymer composition according to any one of [1] to [6], wherein when a cured coating film obtained by curing the curable polymer composition is stretched to a stretching ratio of 100%, a change in 60° gloss before and after stretching is 30 or less. A laminate having a cured coating film of a curable polymer composition. [8] A laminate having a cured coating film of the curable polymer composition according to any one of [1] to [6], wherein the stretch ratio at which cracks occur in the cured coating film obtained by curing the curable polymer composition is 50% or more. [9] A laminate having a cured coating film of the curable polymer composition according to any one of the items [1] to [6]. Effect of the Invention

[0007] According to the present invention, it is possible to provide a curable polymer composition capable of forming a hard coat layer having excellent antiglare properties and stretchability, and a laminate having a cured coating film thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The curable polymer composition of the present invention is a curable polymer composition comprising a polymer A, a polymer B having a solubility parameter (SP value) different from that of the polymer A and incompatible with the polymer A, and a polyfunctional (meth)acrylate C, and satisfies the following (1) and (2): (1) SPA-SPB≧0.5 (2) Polymer A has an unsaturated double bond and a double bond equivalent of 0.1 mmol / g or more and 4 mmol / g or less. (SPA and SPB represent the solubility parameters of the polymer A and the polymer B, respectively.)

[0009] In the present invention, polymer A and polymer B have different solubility parameters (SP values), and it is necessary that polymer A and polymer B are incompatible. Incompatible means that they are not dissolved in each other. In the present invention, since polymer A and polymer B are incompatible, they undergo phase separation, and fine irregularities are formed on the surface of a cured product containing the curable polymer composition of the present invention, thereby exhibiting antiglare properties.

[0010] In the present invention, by satisfying SPA-SPB≧0.5, polymer A constitutes the recesses and polymer B constitutes the protrusions. If the difference between SPA and SPB is less than 0.5, polymer A and polymer B become compatible, and when forming a cured coating film of the curable polymer composition of the present invention, it becomes difficult to form unevenness, making it difficult to exhibit antiglare properties. From the viewpoint of exhibiting antiglare properties, the difference between SPA and SPB is preferably 0.8 or more, more preferably 1.5 or more, and particularly preferably 2.0 or more.

[0011] In order to make SPB lower than SPA, for example, the side chain of the polymer A may contain many highly polar functional groups. Examples of a method for introducing highly polar functional groups into the side chain include a method of copolymerizing highly polar (meth)acrylate monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, and highly polar acrylamide monomers such as dimethylacrylamide, hydroxyethylacrylamide, and acroylmorpholine. In addition, a method of introducing a hydroxyl group by copolymerizing a (meth)acrylic acid ester monomer having an epoxy group such as glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate glycidyl ether, and then adding an unsaturated carboxylic acid such as (meth)acrylic acid, glycolic acid, and dimethylolpropionic acid, may be mentioned.

[0012] In the present invention, it is necessary that the polymer A has an unsaturated double bond and has a double bond equivalent of 0.1 mmol / g or more and 4 mmol / g or less. If the double bond equivalent is less than 0.1 mmol / g, the scratch resistance of the cured product obtained from the curable polymer composition of the present invention becomes insufficient, and if it exceeds 4 mmol / g, the crosslink density of the polymer A becomes high and the stretchability becomes insufficient. The unsaturated double bond equivalent is preferably from 1 mmol / g to 3 mmol / g, and more preferably from 1.2 mmol / g to 2.5 mmol / g.

[0013] Further, in the present invention, it is preferable to include a polyfunctional (meth)acrylate from the viewpoint of improving scratch resistance. The SP value (SPC) of the polyfunctional (meth)acrylate C satisfies the relationship between the SP value (SPA) of the polymer A and the SP value of the polymer C (SPC), SPC-SPB≦(SPA -SPC) × 2.5 is preferably satisfied. By satisfying this condition, multifunctional ( The affinity of the methacrylate C to the polymer B which forms the convex portions increases, and the crosslink density of the convex portions increases, improving the scratch resistance.

[0014] In the present invention, the solubility parameter (SP value) is a value actually measured by the following method. Weigh out 0.5 g of sample into a 100 ml Erlenmeyer flask, add 10 ml of propylene glycol monomethyl ether to dissolve the resin. While stirring with a magnetic stirrer, add hexane dropwise and determine the amount of hexane added (vh) at which the solution becomes cloudy (cloudy point). Next, determine the amount of deionized water added (vd) at the cloudy point when deionized water is used instead of hexane. From vh and vd, the SP value can be calculated using the formula given in the reference: SUH, CLARKE, JPSA-1, 5, 1671-1681 (1967). In addition, the SPC is calculated by using acetone instead of propylene glycol monomethyl ether in the above-mentioned SPA and SPC measurement methods. If the solubility parameter cannot be determined by the above method, for example, if the sample is not soluble in propylene glycol monomethyl ether or acetone, the solubility parameter is calculated by the method proposed by Fedors et al. Specifically, the solubility parameter can be determined by referring to "POLYMER ENGINEERING AND SCIENCE, FEBRUARY, 1974, Vol. 14, No. 2, ROBERT F. FEDORS. (pp. 147-154)".

[0015] In the present invention, the difference in glass transition temperature between polymer A and polymer B (ΔTg=TgB−TgA) is preferably ΔTg<40° C., and more preferably ΔTg<20° C. By reducing the difference in glass transition temperature between polymer A and polymer B, when a cured product of the curable polymer composition of the present invention is stretched, the entire cured product is stretched uniformly, and a large change in the ratio of the area of ​​convex portions to the area of ​​concave portions before and after stretching can be suppressed, thereby reducing the change in gloss before and after stretching.

[0016] <Polymer A> In the present invention, polymer A constitutes the recesses in the cured product containing the curable polymer composition of the present invention. The polymer A must have an unsaturated double bond. The polymer A having an unsaturated double bond can be produced, for example, by copolymerizing a monomer having an epoxy group with an aliphatic monomer in advance, and then subjecting the resulting copolymer to ring-opening addition with a monomer having both an unsaturated double bond and a carboxyl group. Examples of the monomer having an epoxy group include glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and the like. acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, etc. Glycidyl (meth)acrylate is preferred because of its favorable ring-opening addition reactivity of the oxy group. Examples of the aliphatic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, i-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and the like. acrylate, isobornyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and other (meth)acrylic acid esters; hydroxyl group-containing (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; aromatic ring-containing (meth)acrylic acid esters such as phenoxy (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and o-biphenyloxyethyl (meth)acrylate; and isocyanate group-containing (meth)acrylic acid esters such as (meth)acrylic isocyanate and 2-(meth)acryloyloxyethyl isocyanate. Among the (meth)acrylic monomers, methyl (meth)acrylate, ethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, (meth)acryloylmorpholine, isobornyl (meth)acrylate, benzyl (meth)acrylate, and o-biphenyloxyethyl (meth)acrylate are preferred in terms of exhibiting good curing properties. Examples of monomers containing both an unsaturated double bond and a carboxyl group include (meth)acrylic acid, itaconic acid, 2-acryloyloxyethyl succinate, 2-methacryloyloxyethyl succinate, and 2,2,2-trisacryloyloxymethylethyl phthalate. Among these, (meth)acrylic acid is preferred because of its excellent curability with active energy rays. In the present invention, (meth)acrylic means acrylic or methacrylic.

[0017] Furthermore, in the present invention, from the viewpoint of improving the scratch resistance of the cured coating film, the weight average molecular weight of the polymer A is preferably more than 2,000 and not more than 200,000, more preferably more than 6,000 and not more than 150,000, and particularly preferably more than 40,000 and not more than 100,000. The weight average molecular weight of the polymer A is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0018] In the present invention, in terms of improving the curability, the content of the polymer A is preferably 30 to 90 parts by mass, more preferably 40 to 85 parts by mass, and still more preferably 50 to 80 parts by mass, based on 100 parts by mass of the curable polymer composition.

[0019] <Polymer B> In the present invention, polymer B constitutes the convex portions of the cured product containing the curable polymer composition of the present invention. Examples of the monomer constituting the polymer B include styrene-based monomers such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, pt-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-tensylstyrene, pn-dodecylstyrene, p-phenylstyrene, and 3,4-dicyclosilstyrene; methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (Meth)acrylates, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, i-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate and other (meth)acrylic acid esters. Examples of the monomers include aryl monomers. Among these, styrene, methyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc. are preferred because they easily reduce the SP value and exhibit good antiglare properties.

[0020] In the present invention, from the viewpoint of improving the scratch resistance of the cured coating film, the weight average molecular weight of the polymer B is preferably from more than 2,000 to 200,000, more preferably from more than 6,000 to 150,000, and particularly preferably from more than 40,000 to 100,000. The average molecular weight of the polymer B is a value measured by gel permeation chromatography (GPC) and converted into standard polystyrene.

[0021] The polymer B can be produced by a general polymerization method such as a photopolymerization method or a suspension polymerization method.

[0022] In the present invention, in order to achieve both antiglare properties and transparency of the curable polymer composition, the content of the polymer B is preferably 5 to 40 parts by mass, more preferably 15 to 30 parts by mass, based on 100 parts by mass of the curable polymer composition.

[0023] <Polyfunctional (meth)acrylate C> In the present invention, the polyfunctional (meth)acrylate C is a compound having a (meth)acryloyl group and having two or more unsaturated double bonds in one molecule, and examples of the polyfunctional (meth)acrylate C include a dealcoholization reaction product of a polyhydric alcohol and a (meth)acrylate, a urethane (meth)acrylate oligomer, a polyester (meth)acrylate oligomer, a low molecular weight product of the resin listed in the polymer B, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc. Among these, urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol penta(meth)acrylate are preferred in terms of high scratch resistance or good curability of the resulting cured product.

[0024] In the present invention, in order to achieve both stretchability and scratch resistance, the content of the polyfunctional (meth)acrylate C is preferably 1 to 49 parts by mass, more preferably 15 to 40 parts by mass, and even more preferably 25 to 35 parts by mass, relative to 100 parts by mass of the curable polymer composition.

[0025] <Curable polymer composition> The curable polymer composition of the present invention may contain an organic solvent, a polymerization initiator, a leveling agent, inorganic particles, and other components.

[0026] <Organic solvent> The curable polymer composition of the present invention preferably contains both an organic solvent (solvent X) which is a good solvent for both polymer A and polymer B, and an organic solvent (solvent Y) which is a good solvent for polymer A but a poor solvent for polymer B. By containing the organic solvent, the workability in coating the curable polymer composition and the antiglare property of the cured coating film are improved.

[0027] <Solvent X> Examples of the solvent X include acetone, methyl ethyl ketone, methyl propyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, and diacetone alcohol. alcohol-based solvents such as pentanol, hexanol, heptanol, and octanol; ether-based solvents such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, and propylene glycol monomethyl ether acetate; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, methoxybutyl acetate, amyl acetate, propyl acetate, ethyl lactate, methyl lactate, and butyl lactate; and hydrocarbon-based solvents such as toluene, xylene, and solvent naphtha.

[0028] <Solvent Y> Solvent Y is preferably a good solvent for polymer A and a poor solvent for polymer B. A poor solvent for polymer B means that the solvent Y is a solvent in which polymer B does not dissolve. Examples of the solvent Y include alcohol solvents such as methanol, ethanol, butanol, isobutanol, and propyl alcohol; acetone, methyl ethyl ketone, and methyl propyl alcohol; Ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone diacetone ether-based solvents such as normal propyl alcohol, diethylene glycol monomethyl ether, and propylene glycol monomethyl ether; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, methoxybutyl acetate, amyl acetate, propyl acetate, ethyl lactate, methyl lactate, and butyl lactate; and hydrocarbon-based solvents such as toluene, xylene, solvent naphtha, hexane, cyclohexane, ethylcyclohexane, methylcyclohexane, heptane, octane, and decane.

[0029] <Photopolymerization initiator> The curable polymer composition of the present invention preferably contains a photopolymerization initiator. Examples of the photopolymerization initiator include 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2,2-dimethoxy-1,2-diphenylethan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, etc. These polymerization initiators may be used alone or in combination of two or more.

[0030] <Leveling agent> The polymer composition of the present invention preferably contains a leveling agent. Specific examples of the leveling agent include acrylic leveling agents, silicone leveling agents, and fluorine-based leveling agents. Examples of the acrylic leveling agent include the Polyflow series manufactured by Kyoeisha Chemical Co., Ltd.

[0031] Examples of silicone-based leveling agents include the Polyflow series manufactured by Kyoeisha Chemical Co., Ltd., the BYK series manufactured by BYK Chemie, the Silface SAG series manufactured by Nissin Chemical Industry Co., Ltd., the FG series, L series, SH series, and SF series manufactured by Dow Corning Toray Co., Ltd., and SILWETL manufactured by Momentive Performance Materials Japan, Ltd.

[0032] Examples of fluorine-based leveling agents include the Megafac series manufactured by DIC Corporation, the Floren series manufactured by Kyoeisha Chemical Co., Ltd., the Futergent series manufactured by Neos Corporation, and DSN-403N and NS-9013 manufactured by Daikin Co., Ltd. The leveling agents may be used alone or in combination of two or more kinds.

[0033] <Inorganic particles> The polymer composition of the present invention preferably contains inorganic particles. Examples of inorganic particles include silica (including organosilica sol), alumina, titania, zeolite, mica, synthetic mica, calcium oxide, zirconium oxide, zinc oxide, magnesium fluoride, smectite, synthetic smectite, vermiculite, ITO (indium oxide / tin oxide), ATO (antimony oxide / tin oxide), tin oxide, indium oxide, antimony oxide, etc., and among these, silica is preferred. The inorganic particles listed above may be used alone or in combination of two or more. In terms of improving hardness, the inorganic particles are preferably blended in the polymer composition of the present invention as inorganic particles whose surfaces have been modified with a silane coupling agent.

[0034] The average primary particle size of the inorganic particles is usually 1 μm or less, preferably 200 nm or less, more preferably 100 nm or less. The lower limit of the average primary particle size of the inorganic particles is not particularly limited, but is usually 5 nm or more, preferably 10 nm or more. When inorganic particles having an average primary particle size of more than 1 μm are used, sedimentation occurs due to the weight of the particles, and the storage stability of the coating liquid of the curable polymer composition is likely to decrease.

[0035] The average primary particle size of the inorganic particles in the present invention refers to the average value of particle sizes observed by an electron microscope such as a TEM.

[0036] <Other ingredients> To the curable polymer composition of the present invention, an antistatic agent such as a compound containing a thiol group, a plasticizer, a surfactant, an antioxidant, an ultraviolet absorber, etc. may be added within a range that does not impair the effects of the present invention.

[0037] The curable polymer composition of the present invention can be produced by mixing the respective components in a general mixer.

[0038] <Cured Product of Curable Polymer Composition> The cured product of the curable polymer composition of the present invention can be obtained by applying the curable polymer composition to a substrate and then irradiating the substrate with active energy rays.

[0039] <Base material> The substrate film onto which the curable polymer composition of the present invention is applied and cured is not particularly limited, but for example, a transparent resin film made of a resin composition such as polyethylene terephthalate, polymethyl methacrylate, polycarbonate, etc. can be used. For the base film, it is preferable to select a resin having a high glass transition temperature in order to improve the heat resistance of the film insert molding. The glass transition temperature of the resin is preferably 100° C. or more and 170° C. or less, more preferably 120° C. or more and 160° C. or less, and even more preferably 140° C. or more and 155° C. or less. When the film insert molding is used as a front panel that requires heat resistance, for example, polymethyl methacrylate, polycarbonate, etc. are preferably used. The substrate film preferably has a total light transmittance of 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0040] <Active energy rays> The curable polymer composition of the present invention can be cured by active energy rays or heating. However, active energy rays are preferred in that the time required for the curing reaction can be shortened, curing can be performed at low temperature, and an antiglare surface can be easily obtained.

[0041] Examples of active energy rays used when curing the composition include infrared rays, visible light, ultraviolet rays, X-rays, electron beams, α rays, β rays, γ rays, etc. From the viewpoint of equipment cost and productivity, it is preferable to use electron beams or ultraviolet rays, and the light source is preferably an electron beam irradiation device, an ultra-high pressure mercury lamp, a high pressure mercury lamp, a medium pressure mercury lamp, a low pressure mercury lamp, a metal halide lamp, an Ar laser, a He-Cd laser, a solid-state laser, a xenon lamp, or a high frequency induction mercury lamp.

[0042] The amount of irradiation of the active energy rays can be appropriately selected depending on the type of active energy rays. For example, when curing is performed by electron beam irradiation, the radiation dose is preferably 1 to 15 Mrad. When curing is performed by ultraviolet radiation, the radiation dose is preferably 50 to 1500 mJ / cm. 2 It is preferable that: The curing may be carried out in an atmosphere of air or an inert gas such as nitrogen or argon.

[0043] In order to obtain good design and functionality after three-dimensional processing, the thickness of the cured coating film in the present invention is appropriately determined according to the intended use, but the lower limit of the thickness of the cured coating film is preferably 0.5 μm or more, more preferably 1 μm or more. In order to obtain good internal curability and three-dimensional processing suitability, the upper limit is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less.

[0044] <Laminate> The laminate having a cured coating film of the curable polymer composition of the present invention means a laminate in which the curable polymer composition is applied to a substrate, dried, and cured with active energy rays, resulting in a cured product of the curable polymer composition laminated on the surface of the substrate. The laminate of the present invention can be obtained by applying the curable polymer composition to a substrate, drying it, and curing it with active energy rays.

[0045] In order to obtain good design and functionality after three-dimensional processing, the thickness of the cured coating film in the present invention is appropriately determined according to the intended use, but the lower limit of the thickness of the cured coating film is preferably 0.5 μm or more, more preferably 1 μm or more. In order to obtain good internal curability and three-dimensional processing suitability, the upper limit is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less.

[0046] <Glossiness of cured coating film> In order to obtain good antiglare properties, when the laminate of the present invention is stretched to a stretch ratio of 100%, the rate of change in 60° gloss before and after stretching is preferably 30 or less, more preferably 15 or less. Here, the term "stretch ratio of 100%" refers to a stretch ratio in which the laminate is stretched in the longitudinal direction to a length 2.0 times the length before stretching. In addition, the rate of change in 60° gloss before and after stretching was determined by measuring the 60° specular gloss (60° gloss) of an unstretched laminate and a laminate with a stretch rate of 100% using a gloss meter VG2000 manufactured by Nippon Denshoku Industries Co., Ltd., and calculating the absolute value of the difference between the 60° specular gloss (60° gloss) of the unstretched laminate and the laminate with a stretch rate of 100%.

[0047] <Elongation rate of cured coating film> In order to obtain good extensibility of the cured coating film, the stretching ratio at which cracks occur in the cured coating film on the surface of a laminate having a cured coating film of the curable polymer composition of the present invention is preferably 50% or more, and more preferably 100% or more. EXAMPLES

[0048] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these. In the following description, "parts" means parts by mass. This was done by the following method.

[0049] <Evaluation method> The coating liquid (curable polymer composition) prepared in the following Examples and Comparative Examples was applied, dried, and cured with active energy rays to produce a cured coating film of the curable polymer composition. The physical properties of the cured coating film were evaluated by the following methods. <Evaluation sample> The coating solution of the curable polymer composition obtained in the examples was applied to a 100 μm thick easily moldable PET film (FT7-100, manufactured by Teijin DuPont Co., Ltd.) using a #20 bar coater, and the resulting coating film was dried for 60 seconds in a hot air dryer heated to 70° C. to volatilize the solvent. Next, the coating film was cured in air using a high-pressure mercury lamp using a UV conveyor manufactured by Toshiba Lighting & Technology Corporation, and the resultant was used as an evaluation sample.

[0050] <Total light transmittance / haze> The total light transmittance and haze of the laminate of the present invention are measured according to JIS Z8722Z (illumination of a transparent object). The values ​​were measured at a wavelength of 550 nm using a Nippon Denshoku SH7000 in accordance with JIS K7361-1 (Test method for total light transmittance of plastic transparent materials) and JIS K7136 (Determination of haze of plastic transparent materials).

[0051] <Glossiness> The gloss of the laminate of the present invention is measured according to JIS Z 8741 by Nippon Denshoku Industries Co., Ltd. The measurement was carried out as 60° specular gloss (60° gloss) using a gloss meter VG2000 manufactured by Epson Corporation.

[0052] <Anti-glare> The laminate of the present invention was lit by a fluorescent lamp from a height of 2.5 m, and the antiglare property (reflection of the fluorescent lamp) was evaluated by visual observation of the appearance. 3 points: The reflected image of the fluorescent light on the surface of the laminate is very blurred, and the outline of the fluorescent light cannot be seen. 2 points: The reflected image of the fluorescent light on the surface of the laminate is blurred, but the outline can be faintly seen. 1 point: The outline of the fluorescent light can be seen from the reflected image of the fluorescent light on the surface of the laminate.

[0053] <Stretching rate> The laminate of the present invention was cut into a width of 10 mm, and stretched using a tensile load measuring machine ("MX2-500N" manufactured by Imada Co., Ltd.) under conditions of a temperature of 140°C, a tensile speed of 40 mm / min, and a chuck distance of 40 mm to measure the breaking elongation (the elongation until a crack was visually observed), and evaluated according to the following criteria. 3 points: Stretching rate is 100% or more. 2 points: Stretch rate is 50% or more but less than 100%. 1 point: stretch rate less than 50%.

[0054] <Change in 60° gloss before and after stretching> The laminate of the present invention was cut to a width of 10 mm, and the 60° gloss value (GA) of the laminate after 100% stretching and the 60° gloss value (GB) of the laminate before stretching were measured using a tensile load measuring machine (MX2-500N manufactured by Imada Co., Ltd.) under conditions of a temperature of 140° C., a tensile speed of 40 mm / min, and a chuck distance of 40 mm. The difference between GB and GA (ΔGE (ΔGE=absolute value of GB-GA)) was calculated and evaluated according to the following criteria. 3 points:ΔGE≦15.0 2 points: 15.0<ΔGE≦30.0 1 point: 30.0<ΔGE

[0055] <Glare> The laminate of the present invention was attached to an iPad (MD513KH / A) series manufactured by Apple Inc. on which a green image was displayed, and glare of the resin film was evaluated by visual observation from directly above. 2 points: No uneven color caused by glare is observed, and good display visibility is maintained. 1 point: There is color unevenness due to glare, and the visibility of the display is slightly reduced.

[0056] <Scratch resistance> The 60° gloss value of the laminate of the present invention measured before the scratch resistance test was designated as G1. On the other hand, a 200 g weight (area 1.70 cm2) was attached to Bonstar steel wool (#0000) in an atmosphere of 23°C and 55% RH. 2 The cured coating surface was rubbed back and forth 10 times with a Gakushin abrasion tester (manufactured by Toyo Seiki Co., Ltd.), and the 60° gloss value measured immediately after was designated G2. The difference between G2 and G1 (ΔGT (ΔG = absolute value of G2 - G1)) was calculated and evaluated according to the following criteria. 3 points: 6.0<ΔGT≦9.9 2 points: 10.0<ΔGT≦19.9 1 point: 20.0<ΔGT

[0057] <Production Example 1: Synthesis of Polymer A-1 Containing Unsaturated Double Bonds> Into a flask equipped with a thermometer, a stirrer, and a reflux condenser, 376.4 parts of propylene glycol monomethyl ether, 40.0 parts of glycidyl methacrylate, 158.0 parts of methyl methacrylate, 2.0 parts of ethyl acrylate, and 1.2 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) were placed and reacted at 65°C for 3 hours. Then, 0.6 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was further added and reacted for 3 hours, after which 43.6 parts of propylene glycol monomethyl ether and 1.0 part of p-methoxyphenol were added and heated to 100°C. Next, 20.7 parts of acrylic acid and 2.65 parts of triphenylphosphine were added and reacted at 110° C. for 6 hours to obtain a polymer A-1 having a solid content of 35%. Polymer A-1 had an acryloyl equivalent (amount of acryloyl groups introduced) of 1.24 mmol / g and contained 1.24 mmol / g of secondary hydroxyl groups (meth), and also had a glass transition temperature of 84° C., an SP value of 15.0, and a weight average molecular weight of 48,800.

[0058] <Production Example 2: Synthesis of Polymer A-2 Containing Unsaturated Double Bonds> Into a flask equipped with a thermometer, a stirrer, and a reflux condenser, 517.6 parts of propylene glycol monomethyl ether, 110.0 parts of glycidyl methacrylate, 162.3 parts of methyl methacrylate, 2.8 parts of ethyl acrylate, and 1.7 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) were placed and reacted at 65°C for 3 hours. Then, 0.8 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was further added and reacted for 3 hours, after which 101.0 parts of propylene glycol monomethyl ether and 1.4 parts of p-methoxyphenol were added and heated to 100°C. Next, 56.8 parts of acrylic acid and 4.0 parts of triphenylphosphine were added and reacted at 110° C. for 6 hours to obtain a polymer A-2 having a solid content of 35%. Polymer A-2 had an acryloyl equivalent (amount of acryloyl groups introduced) of 2.27 mmol / g and contained 2.27 mmol / g of secondary hydroxyl groups (meth), and also had a glass transition temperature of 55° C., an SP value of 15.8, and a weight average molecular weight of 50,000.

[0059] <Production Example 3: Synthesis of Polymer A-3 Containing Unsaturated Double Bonds> Into a flask equipped with a thermometer, a stirrer, and a reflux condenser, 304.1 parts of propylene glycol monomethyl ether, 196.0 parts of glycidyl methacrylate, 2.0 parts of methyl methacrylate, 2.0 parts of ethyl acrylate, 3.8 parts of mercaptopropyltrimethoxysilane, parts of 2,2'-azobis(2,4-dimethylvaleronitrile) were added and reacted at 65°C for 3 hours. Thereafter, 1.0 part of 2,2'-azobis(2,4-dimethylvaleronitrile) was further added and reacted for 3 hours, after which 271.9 parts of propylene glycol monomethyl ether and 0.9 parts of p-methoxyphenol were added and heated to 100°C. Next, 101.4 parts of acrylic acid and 3.66 parts of triphenylphosphine were added and reacted at 110° C. for 6 hours to obtain a polymer A-2 having a solid content of 35%. Polymer A-3 had an acryloyl equivalent (amount of acryloyl groups introduced) of 4.47 mmol / g and contained 4.47 mmol / g of secondary hydroxyl groups (meth), and also had a glass transition temperature of 32° C., an SP value of 17.4, and a weight average molecular weight of 18,800.

[0060] <Production Example 4: Production of Dispersant> In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 900 parts of deionized water, 60 parts of 2-sulfoethyl sodium methacrylate, 10 parts of potassium methacrylate, and 12 parts of methyl methacrylate were put and stirred, and the temperature was raised to 50°C while replacing the atmosphere in the polymerization apparatus with nitrogen. 0.08 parts of 2,2'-azobis(2-methylpropionamidine) dihydrochloride was added thereto as a polymerization initiator, and the temperature was further raised to 60°C. After the temperature was raised, methyl methacrylate was continuously dropped at a rate of 0.24 parts / min for 75 minutes using a dropping pump. After the dropwise addition was completed, the reaction solution was kept at 60°C for 6 hours and then cooled to room temperature to obtain a dispersant with a solid content of 10% as a transparent aqueous solution.

[0061] <Production Example 5: Synthesis of Polymer B-1> In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 145 parts of deionized water, 0.1 parts of sodium sulfate, and 0.25 parts of a dispersant (solid content 10%) were added and stirred to obtain a uniform aqueous solution. Next, 75 parts of styrene, 25 parts of methyl methacrylate, and 1.5 parts of 2,2'-azobis(2-methylbutyronitrile) were added to obtain an aqueous suspension. Next, the inside of the polymerization apparatus was replaced with nitrogen, the temperature was raised to 75°C and reacted for 1 hour, and in order to further increase the polymerization rate, the temperature was raised to 98°C as a post-treatment temperature and maintained for 30 minutes. Thereafter, the reaction liquid was cooled to 40°C to obtain an aqueous suspension containing a polymer. This aqueous suspension was filtered through a nylon filter cloth with a mesh size of 45 μm, and the filtrate was washed with deionized water, dehydrated, and dried at 50°C for 16 hours to obtain a polymer B-1 incompatible with the polymer A. Polymer B-1 has a glass transition temperature of 93°C, an SP value of 10.2, and a weight average molecular weight of 64. The number was 300.

[0062] <Production Example 6: Synthesis of Polymer B-2> In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 145 parts of deionized water, 0.1 parts of sodium sulfate, and 0.25 parts of a dispersant (solid content 10%) were added and stirred to obtain a uniform aqueous solution. Next, 100 parts of methyl methacrylate, 0.2 parts of octyl mercaptan, and 0.1 parts of 2,2'-azobis(2-methylbutyronitrile) were added to obtain an aqueous suspension. Next, the inside of the polymerization apparatus was replaced with nitrogen, the temperature was raised to 75°C and reacted for 1 hour, and in order to further increase the polymerization rate, the temperature was raised to 98°C as a post-treatment temperature and held for 30 minutes. Thereafter, the reaction liquid was cooled to 40°C to obtain an aqueous suspension containing a polymer. This aqueous suspension was filtered through a nylon filter cloth with a mesh size of 45 μm, and the filtrate was washed with deionized water, dehydrated, and dried at 50°C for 16 hours to obtain a polymer B-2 incompatible with the polymer A. Polymer B-2 had a glass transition temperature of 104° C., an SP value of 13.4, and a weight average molecular weight of 97,300.

[0063] Table 1 shows the SP values ​​and double bond amounts of polymer A, polymer B and polyfunctional (meth)acrylate C used in the curable polymer composition of the present invention, and the glass transition temperatures of polymer A and polymer B.

[0064] [Table 1]

[0065] <Example 1> In a flask equipped with a stirrer, 75 parts of A-1 as polymer A in terms of resin solids, 25 parts of B-1 as polymer B in terms of resin solids, and 3 parts of 1-hydroxy-cyclohexyl-phenyl-ketone (Omnirad 184, manufactured by IGM Resins) as a photoinitiator were added. To this mixture was added a mixed solvent of propylene glycol monomethyl ether, which is a solvent insoluble in polymer B, and methyl ethyl ketone, which is a good solvent for polymers A and B, in a weight ratio of 1:1 to prepare a coating solution with a solid content of 13.0%. This coating solution was applied to a 100 μm thick easily moldable PET film (FT7-100, manufactured by Teijin DuPont Co., Ltd.) using a #20 bar coater, and the solvent was evaporated by drying for 60 seconds in a hot air dryer heated to 70°C. Next, the coating was cured in air using a high-pressure mercury lamp and a UV conveyor manufactured by Toshiba Lighting & Technology Corporation. For photocuring, the integrated light amount of 300 to 390 nm wavelength was measured using an Iwasaki Electric Co., Ltd. illuminometer (Eye UV integrated illuminometer UVPF-A1, PD-365) at 300mJ / cm 2 (250mW / J / cm 2 ) The exposure was adjusted as shown in Fig. 1 and one exposure was performed.

[0066] <Examples 2 to 6 and Comparative Example 1> Except for changing the composition of the curable polymer composition to the formulation shown in Table 2, active energy ray polymerizable compositions were prepared in the same manner as in Example 1, and resin laminates with cured coating films were produced using the compositions and evaluated. The evaluation results of Examples 1 to 6 and Comparative Example 1 are shown in Table 2.

[0067] [Table 2]

[0068] As can be seen from Table 2, Comparative Example 1, in which the double bond equivalent was greater than 4 mmol / g, had poor stretchability and a low overall evaluation score.

Claims

1. A curable polymer composition comprising a polymer A, a polymer B having a solubility parameter (SP value) different from that of the polymer A and incompatible with the polymer A, and a polyfunctional (meth)acrylate C, The polymer A is a (meth)acrylic polymer having a weight average molecular weight of more than 40,000 and not more than 200,000, The polymer B contains at least one of a structural unit derived from a styrene-based monomer and a structural unit derived from a (meth)acrylic acid ester-based monomer, the content of the polymer A is 30 to 90 parts by mass, the content of the polymer B is 5 to 40 parts by mass, and the content of the polyfunctional (meth)acrylate C is 1 to 49 parts by mass, based on 100 parts by mass of the curable polymer composition; A curable polymer composition which satisfies the following (1) and (2): (1) SPA-SPB≧0.5 (2) Polymer A has an unsaturated double bond and a double bond equivalent of 0.1 mmol / g or more and 4 mmol / g or less. (SPA and SPB respectively represent the solubility parameters of the polymer A and the polymer B, and are expressed in units of (cal / cm 3 ) 1 / 2 .)

2. The curable polymer composition described in Claim 1, wherein the polymer B contains a structural unit derived from a (meth)acrylic acid ester monomer.

3. The curable polymer composition according to claim 1 or 2, which satisfies the following (3): (3) SPC-SPB≦(SPA-SPC)×2.5 (SPC indicates the solubility parameter of the polyfunctional (meth)acrylate C, and its unit is (cal / cm 3 ) 1 / 2 .)

4. The curable polymer composition according to any one of claims 1 to 3, wherein the weight average molecular weight of the polymer B is more than 2,000 and not more than 200,000.

5. 5. A laminate having a cured coating film of the curable polymer composition according to any one of claims 1 to 4, wherein when the cured coating film obtained by curing the curable polymer composition is stretched to a stretching ratio of 100%, a change in 60° gloss before and after stretching is 30 or less.

6. A laminate having a cured coating film of the curable polymer composition according to any one of claims 1 to 4, wherein the stretch ratio at which cracks occur in the cured coating film obtained by curing the curable polymer composition is 50% or more.

7. A laminate having a cured coating film of the curable polymer composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Antiglare film

    JP2006106290A

  • Photosensitive resin composition

    JP2008116493A

  • Antiglare hard coat film, and method of manufacturing the same

    JP2009075248A

  • Optical sheet and backlight unit using the same

    JP2011128607A

  • Photopolymerizable composition, and wet area member and functional panel using the same

    JP2012167185A